Language-based identity construction (Ágora de Heterodoxias, 2018)
The study of the intersubjective processes of construction and formation of social identities, as a symbolic and material place of socialization of particular worldviews, idioms of language, gastronomy and, in short, specific ways of life that differentiate people and places in the relational network of near and distant alterities occupies a prominent place in contemporary social theory, with special emphasis on the domains of socio-cognitive, socio-constructionist and language models. The methodology takes place through dialogical reflection, together with the elaboration of percentages on the recurrence of certain cultural practices in different areas of Ecuador.   This article aims to unveil the scope and meaning, both in theory and in concrete reality, of the processes of construction of identities based on language.   All this on the differential perspective of some authors and sociocultural, psychological and anthropological theories. It is argued that to think about the process of identity formation is to focus on the development of learning that urges people to be able to feel, think and act in an educated way, consciously engaging in the economic, political, social and cultural activities of their country. This research concludes that the Province of El Oro is characterized by its cultural diversity, which is a determining factor in the construction of diverse identities composed of three essential elements: subjectivity, language and culture with their varied interrelations.
Keywords: construction of identity; language; social identities; ecuadorian culture